The Effect of Hypnobreastfeeding Technique on the Production of Breast Milk in Postpartum Mothers in Independent Practice Midwives - Rangkuti, Nur Aliyah; Batubara, Novita Sari; Siregar, Rya Anastasya; Suryani, Elvi; Siregar, Ratna Dewi; Harahap, Maryam Latifah (International Journal of Public Health Excellence (IJPHE), 2022)
Breastfeeding is influenced by several factors, including breast milk does not come out immediately after giving birth, the baby's difficulty in sucking, the condition of the mother's nipples being unsupported, the mother working, and the influence/promotion of breast milk substitutes. The purpose of this study was to determine the effect of the hypnobreastfeeding technique on breast milk production in postpartum mothers at BPM Atikah, Panyabungan District. The research design is an analytic experimental pre-experimental type with a pretest-post test one group design approach. all postpartum mothers < 24 hours at BPM Atikah as many as 25 postpartum mothers, the sampling technique was total sampling. The results of the research on breast milk production before the hypnobreastfeeding technique was carried out in postpartum mothers were mostly less than 7-123 ml as many as 12 (48%) and after hypnobreastfeeding in postpartum mothers at BPM Atikah mostly good > 7-123 ml as many as 12 (48%). There is an effect of hypnobreastfeeding technique on milk production with a p value of 0.001 < 0.05. Postpartum mothers should increase their knowledge and experience in an effort to increase breast milk production so that mothers can give breast milk optimally.